Study the Quantitative Expression Pattern of Some Involved Genes on Monoterpenoid Biosynthesis Pathway and Identification of Essential Compounds Affected by Methyl jasmonate in Ajowan Plant - Seyed Ahmad Sadat Noori; Mahsa Jamshidi; mohammad mahdi mortazavian (مجله بیوتکنولوژی کشاورزی, 2019)
Objective Ajowan (Trachyspermum ammi L.) is an annual plant in Apiaceae family which is used in traditional medicine and medical science. This study was carried out to determine the quantitative expression pattern of some genes on monoterpenoid biosynthesis pathway and essential quality in Ajowan treated by methyl jasmonate. Ajowan essential oil compounds and the amount of MECPS, DXR,  and GDs genes expression as main genes related to Thymol biosynthesis pathway in response to methyl jasmonate in 4 different times were analyzed.   Materials and methods After flowering, the 0.1 mM methyl jasmonate hormone was sprayed onto the plants. Samples were taken in 4 times (after 8, 24, and 48 treatment and control treatment). RNA extraction, cDNA synthesis, and Real-Time PCR have done from flowers and the date from these gene expressions were analyzed. Essential chemical compounds were studied by GC-GC/MS. Generally, in 4 samples (samples were taken after 8, 24, and 48 treatment and control treatment), 10 different compounds were distinguished.   Results Based on results, the study of the essential oils of Ajowan showed that the changes of the amount of secondary compounds in the essential oil, the amount of γ-Terpinene (precursor of monoterpenoids like Thymol) went up after 24 hours methyl jasmonate treatment. Due to Real-Time PCR dates, the quantity of all 3 studied genes increased after 24 hours methyl jasmonate treatment. The increasing of these genes expression can be causes the incline level of γ-Terpinene in essential oil.   Conclusions Increasing the amount of 3 mentioned genes expression and also a high amount of γ-Terpinene in essential oils after 24 hours in flowers show that this hormone can affect the gene expression in MEP pathway which causes monoterpenoids production increase after one day of using the hormone.